2014
DOI: 10.4172/2157-7412.1000241
|View full text |Cite
|
Sign up to set email alerts
|

HBV/HCV Infection and Inflammation

Abstract: Liver is a key organ involved in the regulation of both systemic as well as local inflammatory responses. Hepatic inflammation is the hallmark of viral hepatitis caused by non-cytopathic Hepatitis B and C viruses (HBV and HCV). Both HBV and HCV induce several inflammatory responses, causing persistent liver injury, which manifests into progressive diseased state. This ultimately leads to fibrosis, cirrhosis and eventually hepatocellular carcinoma. The disease progression is mediated by a complex interplay of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 159 publications
0
2
0
Order By: Relevance
“…Previously, the medicinal plant Phyllanthus niruri was reported against several diseases which include anti‐babesial, anti‐plasmodial [26], anti‐hyperuricemic [27], anti‐nociceptive [28], anti‐HIV [29] antioxidant, hepatoprotective [30], Vasorelaxant [31] and lipid lowering [32]. It is also used to inhibit platelet aggregation [33], urolithiasis [34], hepatitis B virus, woodchuck hepatitis virus [35]. Zakaria et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the medicinal plant Phyllanthus niruri was reported against several diseases which include anti‐babesial, anti‐plasmodial [26], anti‐hyperuricemic [27], anti‐nociceptive [28], anti‐HIV [29] antioxidant, hepatoprotective [30], Vasorelaxant [31] and lipid lowering [32]. It is also used to inhibit platelet aggregation [33], urolithiasis [34], hepatitis B virus, woodchuck hepatitis virus [35]. Zakaria et al .…”
Section: Resultsmentioning
confidence: 99%
“…Vasorelaxant [31] and lipid lowering [32]. It is also used to inhibit platelet aggregation [33], urolithiasis [34], hepatitis B virus, woodchuck hepatitis virus [35]. Zakaria et al [36] reported that the copyrights to pharmaceutical provisions for treating infections caused by hepatitis B virus (US4673575), hepatitis C virus (EP1294387), adenoviruses (US20060193907) and for treating chronic inflammatory, fibrotic processes (US 6586015).…”
Section: Nirurinmentioning
confidence: 99%